Hubungan Konsumsi Telur Rebus Dengan Kecepatan Kesembuhan Luka Perineum Pada Pasien Postpartum - Aini, Qurratul; Mulyadi, Eko; Satriawati, Arisda Candra (IJMT : Indonesian Journal of Midwifery Today, 2025)
Background: Perineal rupture is a common problem experienced by postpartum mothers in Indonesia. The healing process of perineal wounds can be accelerated by consuming additional nutrients to support recovery.  Objective: This study aims to determine the relationship between boiled egg consumption and the speed of perineal wound healing at PMB DS. Saronggi Sumenep.  Method: A quantitative study using a quasi-experimental design with a one-group post-test only design and purposive sampling technique, involving 40 respondents. Data analysis was conducted using the Chi-Square test, resulting in three categories of wound healing speed.  Results: The study found that 26 respondents had good wound healing, 9 had moderate healing, and 5 had poor healing. The p-value analysis yielded a p-value of 0.001 <0.05.  Conclusion: There is a significant relationship between boiled egg consumption and the rate of perineal wound healing. It is hoped that this study can be used as one consideration in improving the quality of care, particularly in providing counseling to postpartum mothers regarding boiled egg consumption for the rate of perineal wound healing.